Accessing green space in Cape Town : a case study of public perceptions of green space and barriers of access in eight nature reserves and conservation areas within Cape Town - Milliken, Julia (Department of Environmental and Geographical Science, 2015)
In an increasingly urbanised world, addressing the need for access to urban green space has become a pertinent topic of interest. In Cape Town, South Africa, a city of immense biodiversity and unique spatial development, the issue of accessing urban green spaces is particularly important. Environmental and ecological advocates call for conservation of green space, to preserve the rare biodiversity of the region, while pressures for continued development to accommodate the City's growing population override land conservation policy aspirations. The legacy of post-apartheid development is still strongly entrenched in Cape Town, resulting in an inequitable and in efficient city form. Access to quality green space remains problematic in Cape Town. This research seeks to discover how accessible urban green spaces are in Cape Town, and, if barriers exist, whether they are physical, economic, or socially driven. The author has undertaken a case study method approach to conduct this research, focusing on eight nature reserves or conservation areas managed by the City of Cape Town in the southern and eastern suburbs of the City. Key informant interviews (n= 6) were conducted, as well as qualitative and quantitative surveys of park users and the general public. Park users (n= 672) were surveyed on site, at one of the eight green spaces, while the public (n= 317) were surveyed at the nearest commercial shopping area adjacent to the green space. Outcome measures included demographic information, suburb of residence, mode of transport, reasons for choosing mode of transport, frequency of green space visits, and reasons for visiting. Results show the majority of park users accessed the green space by personal vehicle, and very few park users took public transport (n= 3). The majority of users resided in suburbs within two kilometre s of the green space. Park users varied in age, yet young adults aged 16-19 and elderly over the age of 80 accounted for only 2.8% and 1.8% of those surveyed, respectively. The ethnic breakdown of those surveyed was not indicative of Cape Town's ethnic breakdown, according to the 2011 Census, with white South Africans and coloured South Africans accounting for 50% and 39%, respectively. Over a quarter of the public surveyed identified 'lack of information' or 'unaware of what park offers' as the reason for not visiting the green space. Safety and security was a common concern among both park users and the public; many expressed concern about visiting the green space alone, or traveling alone due to issues of security in the adjacent neighbourhoods. From the data gathered in this research, the author concludes that barriers exist in the access of quality green spaces within Cape Town, and include, but are not limited to, issues of proximity, public transport, safety and security, spatial development of the City, varied green space interests, and information barriers. These issues vastly alter how users engage in these eight different green spaces. Further research may be conducted in a more expansive study on Cape Town's green spaces, including small local green spaces in neighbourhoods throughout the City, which may yield interesting results on the access and barriers to access of urban green spaces.